Perfil genotípico do HCV em portadores de hepatite C em Belo Horizonte, Minas Gerais Brasil - Carlos Perone (2007)
Hepatitis C virus (HCV), like other RNA virus, is characterized by a high genomic heterogeneity. To date, six different genotypes have been identified, with distinct geographical distribution. HCV genotype identification is essential in clinical practice, since therapeutic schedule and the probability of viral response are genotype-specific. The referencemethod is direct sequencing of viral genome. The highly conserved 5UTR region is frequently used for diagnostic purposes. Geographical distribution of HCV genotypes in Brazil shows high prevalence of genotype 1, follow by genotypes 3 and 2. However, the prevalence of genotypes and subtypes varies between different regions of the country and remains unknown in some regions. METHODOLOGY: A prospective analysis was carried out from 2002 to 2006 in 788 specimens of patients with chronic hepatitis C sent to a reference laboratory (NUPAD) in Belo Horizonte (MG) Brazil. The HCV genotype test was performed by direct sequencing of the 5UTR region, followed by comparative analysisthrough alignment with reference sequences of main viral genotypes. Additionally, phylogenetic analysis was performed including all representative variants and prototype 5UTR sequences. RESULTS: Genotyping was successful in 777 (98,6%) of 788 samples. Results showed a high prevalence (78,4%) of genotype 1 (1b:, 40,4%; 1a, 37.5% and 1a/b, 0.5%) followed by genotype 3a (17,9%) and 2b (3,1%). Three samples were identified as genotype 2 a/c and two as genotype 4. Phylogenetic analysis showed the expected cosegregation of selected sequences with reference 5UTR sequences of genotypes 1, 2, 3 and 4,except for two samples of genotype 1a. Both genotype 4 sequences had shown greater similarity with subtype 4t. CONCLUSIONS: This work contributed to confirm the effectiveness and accuracy of the methodology used for HCV genotyping in the NUPAD UFMG laboratory. The proportion of sequenced and genotyped samples (98,6%) demonstrated excellent performance of laboratory protocols. The high prevalence of genotype 1 (78,4%) found in Belo Horizonte was similar to the ones reported in other cities, but higher than the one found in São Paulo and the South of Brazil. Phylogenetic analysis provided support to genotyping assay in discriminating genotypes 1, 2 and 3, the most frequent inBrazil. Phylogenetic analysis also confirmed genotype 4 assignment in two samples. The finding of atypical 5UTR strains and mutations suggests the existence of new virus subtypes in our population. Nucleotide sequencing of more informative viral genome regions is needed for accurate classification of those isolates as well as other uncommon genotypes. The results presented here show in detail the genotypic profile of HCV in chronic hepatitis C carriers in Belo Horizonte and strengthen the necessity to increase researches regarding the genetic diversity of HCV in Brazil.